FAKTOR YANG BERPENGARUH TERHADAP HEALTH SEEKING BEHAVIOR KELUARGA DI DESA TUTUL KECAMATAN BALUNG KABUPATEN JEMBER - Fauziyah, fauziyah; Santoso, Teguh Hari; Dewi, Sofia Rhosma (Universitas Muhammadiyah Jember, 2017)
Health is a basic need for everyone. Health Seeking Behavior is the behavior of people or communities who are experiencing illness or other health problems, to get treatment so healed or overcome health. This research use correlation design with cross sectional approach. The goal is to know the factors that influence the health seeking behavior of the family. Population in this research all family in Tutul Village of Balung Jember District. The sampling technique used cluster sampling and data collection techniques using questionnaires. Data analysis in this study used univariate and multivariate with multiple linear test. The result of this research is culture factor (p value = 0.021), education factor (p value = 0.004), disease seriousness factor (p value = 0.024) and insurance coverage factor (p value = 0.000). From the data, it is found that all factors influence the health seeking behavior, but the insurance coverage factor becomes the most dominant factor influencing the health seeking behavior of the family. Therefore, there is a need for attention for government agencies responsible for the equitable distribution of insurance holdings managed by the government.Keyword : The Family, Culture Factor, Education Factor, Disease Seriousness Factor, Insurance Coverage Factor, Health Seeking Behavior.